The Level Of Emotional Intelligence Among Female Teachers At Basic Schools In Jordan Based On Academic Qualification, Teaching Experience, And The Class Taught - Najihah, Abd Wahid; Tahat Maha Hani, Mohammad (2018)
Emotional intelligence affects the instructional performance of teachers at basic schools, as reflected strongly on their pupils. Hence, it is necessary to ascertain the teachers’ level of emotional intelligence and determine the most important factors associated with it. Therefore, the present study aims to determine the level of emotional intelligence among female teachers who teach at the fourth to the tenth basic levels, in order to enable the researchers to provide appropriate proposals and programs for the development of the emotional intelligence amongst the female teachers in general and dealings with students in particular. To achieve the objective of this study, descriptive analytical method was used. A random sample of 92 female teachers at basic schools in Irbid was selected. The study also used the scale proposed by Bar-On and Parker 2000 to measure the level of emotional intelligence amongst the teachers. The reliability and validity of the instrument have been measured. The data were statistically analyzed using mean and standard deviations, as well as analysis of three-dimensional variance. The most important results are: There is high level of emotional intelligence amongst the female teachers, and there are statistically significant differences in the level of emotional intelligence considering the variable of academic qualification, teaching experience and the class taught in all areas of variables of academics qualification, teaching experience and the class taught in all their various disciplines.